Template-free fabrication of hierarchical graphitic carbon nitride via self-assembled aggregates for enhanced photocatalytic hydrogen evolution activity under visible light. Issue 18 (19th August 2020) - Xia, Yingchun; Wang, Deqi; Jia, Ruixin; Xu, Gege; Zhan, Junjie; Lu, Yanbing; Xu, Weijian
Abstract : A structure-retention strategy for hierarchical graphitic carbon nitride with enhanced photocatalytic hydrogen evolution activity by direct calcination of self-assembled melamine aggregates. Abstract : Structure and shape engineering has great potential to enable unique graphitic carbon nitride (CN) nanostructures with adjustable electronic properties and enhanced photocatalytic activities. In this study, a novel type of self-assembled melamine aggregate was formed in dimethyl sulfoxide (DMSO) without additional chemicals and templates, and these aggregates were then directly calcined to obtain three-dimensional hierarchically nanoporous CN. This structure-retention from the precursor to CN demonstrated that the structure and shape of CN were free from collapse during melamine thermal polycondensation and thus exposed vast active sites. Besides, the oxygen dopant resulting from structure-retention adjusted the electronic properties of CN derived from melamine aggregates (MACN), facilitating the hydrogen evolution reaction. The Pt-decorated MACN showed the fastest hydrogen production rate of 8.2 μmol h −1 for 3 wt% Pt/MACN under visible light, which is 4.5 times higher than that of the Pt-decorated CN sample obtained from the calcination of commercial melamine precursor. The structure-retention strategy via melamine self-assembly is a facile, rapid, and robust method to access unique nanostructured CN with enhanced photocatalytic performance under visible light, thereby enriching the toolbox for the fabrication of CN materials.